PENGARUH KONSENTRASI KLORAMFENIKOL TERHADAP ADSORPSI POLIMER CETAK MOLEKUL DENGAN METODE PRESIPITASI - Ainun Rachmatina Atqa; Maria Monica Sianita (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2021)
The aims of this study to synthesize Molecularly Imprinted Polymer (MIP) which can be used as adsorbents for chloramphenicol adsorption (CAP). The performance of the MIP adsorbent was tested for adsorption with variations in the initial CAP concentration. The CAP concentrations used were 10, 25, and 50 ppm. The characterization of the resulting MIP, Non-Imprinted Polymer (NIP), and Blank Polymer (PB) were analyzed using Fourier Transform Infrared (FTIR), to determine the -NO2 group. The results showed that the greater the initial CAP concentration, the higher the adsorption capability in MIP and PB. The largest adsorption capability in this study for MIP was 16.54 mg/g and PB was 8.78 mg/g at a concentration of 50 ppm. MIP has a higher adsorption capability than PB due to the specific adsorption of MIP to CAP. The imprinting factor (IF) value obtained is 1.88. FTIR results showed the presence of –NO2 group at wave number 1560.62 cm-1 in MIP with a lower intensity than NIP. This indicates the presence of CAP that has been eluted in the extraction process. Key words: Molecularly Imprinted Polymer, chloramphenicol, adsorption